Spontaneous regression of laryngeal squamous cell carcinoma: an unknown occurrence: a rare case report - Navneet Agarwal; Diksha Gupta (The Egyptian Journal of Otolaryngology, 2021)
Abstract Background Spontaneous regression of squamous cell carcinoma is extremely rare and a very challenging phenomenon. Here, we are presenting such a rare case of biopsy-proven laryngeal squamous cell carcinoma who underwent tracheostomy and later the growth regressed without any treatment. Case presentation A histologically proven laryngeal squamous cell carcinoma where the tumour initially leads to the tracheostomy as it compromised the airway and later on the patient presented with the accidental decannulation and the laryngoscopy showed regression of the tumour to the extent that the patient did not require retracheostomy before undergoing radiotherapy. Here, vascular insufficiency of large tumour could have necrosed the tumour along with other factors. Conclusion This case shows the existence of endogenous control in the host against the tumour. A greater understanding of these controlling factors may help us in the future.